Advances in the Application of Supramolecular Hydrogels for Stem Cell Delivery and Cartilage Tissue Engineering - Yan, Xin; Chen, You-Rong; Song, Yi-Fan; Ye, Jing; Yang, Meng; Xu, Bing-Bing; Zhang, Ji-ying; Wang, Xing; Yu, Jia-Kuo (Frontiers in Bioengineering and Biotechnology, 2020)
Cartilage defects pose a great threat to the health of aging population. Cartilage has limited self-regeneration ability because it lacks blood vessels, nerves and lymph. To achieve efficient cartilage regeneration, supramolecular hydrogels are used in medical applications and tissue engineering as they are tunable and reversible in nature. Moreover, they possess supramolecular interactions which allow incorporation of cells. These hydrogels present great potential for tissue engineering-based therapies. This review presents advances in the development of stem cell-laden supramolecular hydrogels. We discuss new possibilities for stem cell therapy and their uses in cartilage tissue engineering. Gray areas and future perspectives are discussed.